2011
DOI: 10.1007/s11250-011-9869-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA diversity, origin, and phylogenic relationships of three Chinese large-fat-tailed sheep breeds

Abstract: China is abundant of sheep genetic resources. A total of 55 sequences containing the Ovis aries mtDNA D: -loop of three large-fat-tailed sheep breeds, named Lanzhou, Tong, and Han were retrieved from GenBank to investigate their genetic diversity, origin, and phylogenetic evolution. The results showed that the sheep breeds in our study proved to be extremely diverse, the average haplotype diversity and nucleotide diversity were 0.987 ± 0.006 and 0.03956 ± 0.00206, respectively. The 55 sequences gave 39 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
5
17
0
Order By: Relevance
“…In general, the haplogroup prevalence in present study is consistent with the previous studies on domestic sheep breeds in Asia (Luo et al, 2005;Chen et al, 2006;Pardeshi et al, 2007;Wang et al, 2007;Zhao et al, 2011;Arora et al, 2013;Singh et al, 2013). Since haplogroup A is most predominant in Asia, it is difficult to understand the direction of its gene flow.…”
Section: Genetic Diversitysupporting
confidence: 88%
See 1 more Smart Citation
“…In general, the haplogroup prevalence in present study is consistent with the previous studies on domestic sheep breeds in Asia (Luo et al, 2005;Chen et al, 2006;Pardeshi et al, 2007;Wang et al, 2007;Zhao et al, 2011;Arora et al, 2013;Singh et al, 2013). Since haplogroup A is most predominant in Asia, it is difficult to understand the direction of its gene flow.…”
Section: Genetic Diversitysupporting
confidence: 88%
“…Diversity of mitochondrial DNA (mtDNA) has been widely used to assess the origin, phylogeny and population structure of sheep breeds all over the world (Hiendleder et al, 1998a(Hiendleder et al, , 1998b(Hiendleder et al, , 2002Meadows et al, 2005Meadows et al, , 2007Pedrosa et al, 2005Pedrosa et al, , 2007Pereira et al, 2006;Tapio et al, 2006;Oner et al, 2013), specifically in China (Guo et al, 2005;Luo et al, 2005;Chen et al, 2006;Wang et al, 2007;Sulaiman et al, 2011;Zhao et al, 2011) and India (Pardeshi et al, 2007;Arora et al, 2013;Singh et al, 2013). In contrast, information on phylogeography of Nepalese sheep mtDNA is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with archeological data and other genetic diversity studies [21,[40][41][42][43], while in this study, the haplotype diversity was higher than that found in a previous study [44], and the nucleotide diversity was lower compared with the data in a previous study [7]. The genetic diversity among the 15 Tibetan sheep populations was relatively higher compared with other sheep populations [1,44]. For instance, the haplotype diversity values of Turkish sheep breeds distributed in a Turkish population were 0.95 ± 0.01 [44].…”
Section: High Mtdna D-loop Diversity Of Tibetan Sheep Populationssupporting
confidence: 91%
“…In China, Tibetan sheep (Ovis aries) play an important role in agriculture, economy, culture and religion in Qinghai-Tibetan Plateau areas, and provide meat, wool, and pelts for local populations [1]. Due to the rich Tibetan sheep genetic resources, there are approximately 17 indigenous sheep populations in the Qinghai-Tibetan Plateau area.…”
Section: Introductionmentioning
confidence: 99%
“…With the advantages of high PIC, uniform distribution in genome, and easy location, the microsatellite markers have been widely used in genetic map construction, gene location, relative relationship identification, population genetic structure analysis and marker assisted selection, etc. The polymorphic analysis of microsatellite markers played an important role in assessment of sheep genetic diversity and classification, conservation and utilization of breeds, and has been widely applied to study the genetic variation of different sheep breeds (Gizaw et al, 2007;Ozerov et al, 2008;Glowatzki-Mullis et al, 2009;Maria et al, 2010;Arora et al, 2011;Zhao et al, 2011;Sun et al, 2011;Al-Barzinji et al, 2011;Tolonea et al, 2012;Ghazy et al, 2013). Recently, Soma et al (2012) analyzed population genetic structure of the South African sheep breeds by microsatellite markers.…”
Section: Introductionmentioning
confidence: 99%